Characterization of Equivalent Black Carbon at a regional background site in Central Europe: Variability and source apportionment☆ - Mbengue, Saliou; Serfozo, Norbert; Schwarz, Jaroslav; Ziková, Nadezda; Šmejkalová, Adéla Holubová; Holoubek, Ivan (Environmental pollution (1987), 2020)
Characterizing Black Carbon (BC) at regional background areas is important for better understanding its impact on climate forcing and health effects. The variability and sources of Equivalent Black Carbon (EBC) in PM10 (atmospheric particles with aerodynamic diameter smaller than 10 μm) have been investigated during a 5-year measurement period at the National Atmospheric Observatory Košetice (NAOK), Czech Republic. Ground based measurements were performed from September 2012 to December 2017 with a 7-wavelength aethalometer (AE31, Magee Scientific). The contributions of fossil fuel (EBCff) and biomass burning (EBCbb) were estimated using the aethalometer model. Seasonal, diurnal and weekly variations of EBC were observed that can be related to the sources fluctuations and transport characteristic of pollutants predominantly associated with regional air masses recirculating over the Czech Republic and neighboring countries. The absorption Ångström exponent (α-value) estimated in summer (1.1 ± 0.2) was consistent with reported value for traffic, while the mean highest value (1.5 ± 0.2) was observed in winter due to increased EBCbb accounting for about 50% of the total EBC. This result is in agreement with the strong correlation between EBCbb and biomass burning tracers (levoglucosan and mannosan) in winter. During this season, the concentrations of EBCbb and Delta-C (proxy for biomass burning) reached a maximum in the evening when increasing emissions of wood burning in domestic heating devices (woodstoves/heating system) is expected, especially during the weekend. The diurnal profile of EBCff displays a typical morning peak during the morning traffic rush hour and shows a decreasing concentration during weekends due to lower the traffic emission.
Keywords: aerosoly; Environmental Monitoring; Particulate Matter; látky znečišťující vzduch; monitorování životního prostředí; Carbon; pevné částice; roční období; uhlík; Česká republika; Air Pollutants; Aerosols; Seasons; Czech Republic